Analysis Of Factors Affecting Auditor Switching In Manufacturing Companies Listed On The Indonesia Stock Exchange - Lora Ferbina Bangun (TRIGIN PUBLISHER, 2021)
Auditor switching is the turn of KAP and auditor carried out by the company for a reason or there are certain factors of the company or of the auditor itself. This study aims to determine the effect of audit fees, financial distress auditor size, client size, and management change to the auditor switching on manufacturing companies listed in the Indonesia Stock Exchange 2011-2014 period. This study used secondary data obtained from financial statements published on the internet through the official website of Indonesia Stock Exchange www.idx.co.id.The research sample is manufacturing companies listed in the Indonesia Stock Exchange 2012-2014. Sampling using purposive sampling and obtained a sample of 96 observations of 32 companies sampled in this study. Hypothesis testing is done by using logistic regression. From the test results indicate that audit fees, financial distress, auditor sie, clients size, and management changes do not influence auditor switching.